English Pronunciation Teaching and Research Contemporary Perspectives - Pennington, Martha C.; Rogerson-Revell, Pamela; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This collaborative work by two-well-known pronunciation specialists breaks new ground in presenting an applied, sociolinguistic orientation to pronunciation teaching and research that is both up-to-date and comprehensive in scope. It is a welcome addition to the pronunciation literature that should be on the reading lists of all language teachers and applied linguists." -Rodney H. Jones, University of Reading, UK "This book makes a valuable contribution by connecting research and practice while providing a comprehensive scope. This is much appreciated given the extensive amount of research in the field as well as in related areas." -Jose Antonio Mompean Gonzalez, University of Murcia, Spain This book offers contemporary perspectives on English pronunciation teaching and research in the context of increasing multilingualism and English as an international language. It reviews current theory and practice in pronunciation pedagogy, language learning, language assessment, and technological developments, and presents an expanded view of pronunciation in communication, education, and employment. Its eight chapters provide a comprehensive and up-to-date analysis of pronunciation and the linguistic and social functions it fulfils. Topics include pronunciation in first and second language acquisition; instructional approaches and factors impacting teachers' curriculum decisions; methods for assessing pronunciation; the use of technology for pronunciation teaching, learning, and testing; pronunciation issues of teachers who are second-language speakers; and applications of pronunciation research and pedagogy in L1 literacy and speech therapy, forensic linguistics, and health, workplace, and political communication. The chapters also critically examine the research base supporting specific teaching approaches and identify research gaps in need of further investigation. This rigorous work will provide an invaluable resource for teachers and teacher educators; in addition to researchers in the fields of applied linguistics, phonology and communication. Martha C. Pennington is Professorial Research Associate in Linguistics at the School for Oriental and African Studies and a Research Fellow in Applied Linguistics and Communication at Birkbeck College, both of the University of London, UK. Pamela Rogerson-Revell is Associate Professor in Applied Linguistics at the University of Leicester, UK.
Chapter 1: The Nature of Pronunciation -- Chapter 2: Phonology in Language Learning -- Chapter 3: Framing the Teaching of Pronunciation -- Chapter 4: Pronunciation in the Classroom: Teachers and Teaching Methods -- Chapter 5: Using Technology for Pronunciation Teaching, Learning, and Assessment -- Chapter 6: Assessing Pronunciation -- Chapter 7: Beyond the Language Classroom: Wider Applications of Pronunciation Research and Practice -- Chapter 8: Relating Pronunciation Research and Practice.
Keywords: Applied linguistics; Grammar, Comparative and general -- Phonology; Linguistics -- Methodology; Language and languages -- Study and teaching; Multilingualism; Language policy; Applied Linguistics; Phonology and Phonetics; Research Methods in Language and Linguistics; Language Teaching and Learning; Multilingualism; Language Policy and Planning